PHYSICOCHEMICAL CONDITIONS OF FORMATION OF EPITHERMAL GOLD-MERCURY DEPOSITS - Naumov E.A.; Borovikov A.A.; Borisenko A.S.; Zadorozhniy M.V.; Murzin V.V. (My University, 2002)
Fluid inclusions in minerals from more than 22 Au-Hg deposits (Central Asia, Urals, East Sayan, Gorny Altai, northeastern Russia, Mongolia, etc.) have been examined by thermobarogeochemical methods (thermo- and cryometry, Raman spectroscopy of gas phase). It has been established that Au-Hg deposits are low-temperature (280-50 degreesC) hydrothermal objects which formed in subsurface (volcanogenic-hydrothermal) or shallow-depth (plutonogenic-hydrothermal) conditions, under pressures lower than 500-600 bars. The volcanogenic-hydrothermal Au-Hg deposits were formed with participation of weakly concentrated (10-0.5, less frequently, to 14 wt.%) chloride or chloride-bicarbonate-sodium hydrothermal fluids with low-density N-2-CO2 (+/-CH4) gas phase. The ore-forming fluids of plutonogenic-hydrothermal deposits are characterized by wider variations in concentration (from 0.2 to 25 wt.%), complex salt composition (NaCl, CaCl2, FeCl2, KCl, etc.), and dense high-CO2 gas phase (CO2 > N-2 > CH4); in salt composition and reduced character they are similar to magmatic fluids. The characteristic feature of the fluid regime of ore-forming systems of volcanogenic- and plutonogenic-hydrothermal Au-Hg deposits is the heterogeneous, state of ore-forming fluids. In particular ore districts, the physicochemical parameters of formation of volcanogenic- and plutonogenic-hydrothermal Au-Hg deposits are generally close to the parameters of formation of similar Au-Sb, Sb, and Sb-Hg deposits. The results obtained from the thermobarogeochemical study stress the polygene nature of Au-Hg deposits.